122 An intervention to alter help-seeking behaviour and reduce pre-hospital delay time in patients diagnosed with acute coronary syndrome (ACS). (16th May 2012) - Mooney, M; O'Brien, F; McKee, G; Donnell, S O'; Moser, D
Abstract : Introduction: The problem of pre-hospital delay among patients with acute coronary syndrome remains unresolved despite past attempts to contain the problem. Mortality and morbidity could be reduced if patients sought earlier treatment for symptoms. Median pre-hospital delay times ranging from 1.0 h to 15.2 h have been reported in the literature. Most of the reported pre-hospital delay times extend beyond the parameters outlined in the European Society of Cardiology guidelines. Methods: A randomised controlled trial was used to test the effectiveness of an educational intervention on pre-hospital delay time and help-seeking behaviours including contacting the general practitioner, use of nitrates, use of ambulance and time taken to notify someone in response to ACS symptoms. The intervention group were given a 30-min individualised education session which focused on: education about heart disease misconceptions, stimulating behavioural change through motivational techniques and the provision of a tailored action plan for future use. This intervention was reinforced 1 month later by telephone. Operational definition: Pre-hospital delay time was defined as the time from acute symptom onset until arrival at the emergency department. Research instrument: Response to Symptoms Questionnaire. Results: Pre-hospital delay time was initially recorded on 1944 patients (control: 972; intervention: 972). Of these, 314 patients were readmitted to an emergency department with ACS symptoms (control: 137; intervention: 177). We again measured their pre-hospital delay times. The readmission diagnoses were: control group: (STEMI: 24.8%; NSTEMI 25.5%, unstable angina 49.6%) and intervention group: (STEMI 24.3%; NSTEMI 35.0%; unstable angina 40.7%). Data were collected using patient interviews and pre-hospital delay times were subsequently verified from the case notes. Allowing for the covariate of education, on which the two groups differed, we used repeated measures ANCOVA on log transformed delay-time. Those in the intervention group demonstrated a significant decrease in pre-hospital delay time compared to both their own baseline (p<0.001) and to that of the control group (p=0.04). The intervention group also had a lower rate of consultation with a general physician before attending the emergency department (p=0.024) and were quicker to report the presence of symptoms to another individual (p=0.010). The groups did not differ on the use of ambulance (p=0.510) or nitrates (p=0.058). Conclusions/Implications: This RCT demonstrated that it is possible to reduce pre-hospital delay time in patients diagnosed with ACS. This can be achieved through an individualised educational intervention that focuses on symptom identification and the appropriate actions to take in this situation. There is a need for renewed and continued emphasis on the importance of ambulance use when ACS symptoms arise.